Physical Activity and Nutrition Intervention for Mothers of Young Children: Process Evaluation - Monteiro, S.; Jancey, Jonine; Howat, Peter (Open Access, 2014)
Introduction: Process evaluation of community based projects is integral to understanding the success or failure of health promotion interventions. Process evaluation was used to assess the intervention strategies and resources in a playgroup setting aimed at mothers of young children. Methods: Process evaluation data were collected from participants (n = 249) and staff (n = 25) involved in the intervention. Data included staff perspectives on use of the playgroup as a setting, participants’ views on the feasibility and acceptability of the program strategies and resources, and program reach. Results: Responding participants reported that the intervention was useful (98%) and relevant for their age group (92%), encouraged them to think about making changes to their physical activity (95%) and dietary (98%) behaviors, and helped them to make changes to their physical activity (66%) and dietary (79%) behaviors. Participants reported that the most useful intervention strategies included the program booklet (85%), workshops (86%), newsletters (73%) and SMS (57%).Conclusion: This research provides valuable information on participants’ perspectives of the program strategies, content and overall implementation. It provides insight into the feasibility and acceptability of the intervention and identifies areas for improvement when conducting programs in playgroup settings. The process evaluation indicated that playgroups are a suitable setting for health promotion targeting mothers of young children.